Ectopic Expression of the Grape Hyacinth (Muscari armeniacum) R2R3-MYB Transcription Factor Gene, MaAN2, Induces Anthocyanin Accumulation in Tobacco - Chen, Kaili; Liu, Hongli; Lou, Qian; Liu, Yali (Frontiers in Plant Science, 2017)
Anthocyanins are responsible for the different colors of ornamental plants. Grape hyacinth (Muscari armeniacum), a monocot plant with bulbous flowers, is popular for its fascinating blue color. In the present study, we functionally characterized an R2R3-MYB transcription factor gene MaAN2 from M. armeniacum. Our results indicated that MaAN2 participates in controlling anthocyanin biosynthesis. Sequence alignment and phylogenetic analysis suggested that MaAN2 belonged to the R2R3-MYB family AN2 subgroup. The anthocyanin accumulation of grape hyacinth flowers was positively correlated with the expression of MaAN2. And the transcriptional expression of MaAN2 was also consistent with those of M. armeniacum dihydroflavonol 4-reductase (MaDFR) and M. armeniacum anthocyanidin synthase (MaANS) in flowers. A dual luciferase transient expression assay in Nicotiana benthamiana leaves indicated that MaAN2 interacted with Arabidopsis thaliana TRANSPARENT TESTA8 (AtTT8) and strongly activated the promoters of MaDFR and MaANS, but not the promoters of M. armeniacum chalcone synthase, M. armeniacum chalcone isomerase, and M. armeniacum flavanone 3-hydroxylase. Bimolecular fluorescence complementation assay confirmed that MaAN2 interacted with AtTT8 in vivo. The ectopic expression of MaAN2 in Nicotiana tabacum resulted in obvious red coloration of the leaves and much redder flowers. Almost all anthocyanin biosynthetic genes were remarkably upregulated in the leaves and flowers of the transgenic tobacco, and NtAn1a and NtAn1b (two basic helix–loop–helix anthocyanin regulatory genes) were highly expressed in the transformed leaves, compared to the empty vector transformants. Collectively, our results suggest that MaAN2 plays a role in anthocyanin biosynthesis.